Reducing Hematologic Toxicity With Short Course Postexposure Prophylaxis With Zidovudine for HIV-1 Exposed Infants With Low Transmission Risk. Issue 7 (July 2019) - Nguyen, Thi Thanh Truc; Kobbe, Robin; Schulze-Sturm, Ulf; Blohm, Martin; Hollwitz, Bettina; Hertling, Sandra; Becker, Christina; Oommen, Prasad Thomas; Laws, Hans-Jürgen; Martignoni, Franca; Ole Jensen, Björn-Erik; Olah, Karen; et al.
Abstract : Using retrospectively collected data from 383 infants born to HIV-1-infected mothers receiving antiretroviral therapy, we compared transmission rates and hematologic toxicity between infants receiving 2-week (short course) versus longer duration zidovudine postexposure prophylaxis. Short course resulted in lower hematologic toxicity without evidence of increased vertical transmission risk.